Effect of rare earth elements and their oxides on tribo-mechanical performance of laser claddings: A review - Quazi, M.M.; Fazal, M.A.; Haseeb, A.S. Md. Abdul; Yusof, F.; Masjuki, Haji Hassan; Arslan, A. (Elsevier, 2016)
Laser cladding is a promising photon-based surface engineering technique broadly utilized for fabricating harder and wear resistant composite coatings. In spite of excellent properties, the practical applications of laser claddings are relatively restricted when compared with well-established coating techniques because of their inherent defects identified as cracks, pores and inclusions. Substantial evidence suggests that the incorporation of an appropriate amount of rare earth in laser claddings can remarkably prevent these defects. Additionally, the presence of rare earth in laser claddings can notably enhance tribo-mechanical properties such as surface hardness, modulus of elasticity, fracture toughness, friction coefficient and wear rate. In this literature review, the effect of rare earth in reducing dilution and cracks susceptibility of laser claddings in addition to microstructural refinement attained was examined. Mechanical and tribological properties of these claddings along with their underlying mechanism were discussed in detail. Finally, this article summarizes current applications of laser claddings based on rare earth and was concluded with future research directions.